IMPROVED ANECDOTAL TEXT WRITING SKILLS THROUGH MODEL DISCOVERY LEARNING ASSISTED BY CANVA APPLICATIONS - Doa, Maria Goreti; Ulfah, Ulfah; Asrianti, Asrianti; Ruslan, Hasnur; Santosa, Pratama Bayu (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the improvement of anecdotal text writing skills through the implementation of the Discovery Learning model assisted by the Canva application among ninth-grade students at SMPN 3 Luwuk Timur. The background of this research is based on the low ability of students to write anecdotal texts, which had not yet reached the minimum mastery standard, as well as the need for innovative learning approaches that can enhance students’ creativity and motivation. The research employed a descriptive quantitative approach with a classroom action research (CAR) design conducted over two cycles. The subjects of this study were all ninth-grade students at the school, totaling 23 participants. Data collection was carried out through anecdotal writing performance tests administered at the end of each cycle. Quantitative data analysis involved calculating the percentage of completeness, class average scores, and improvement in learning outcomes between cycles. The evaluation results in Cycle I showed an average score of 69.34 with a completeness rate of 52.17%. After improvements in the learning process during Cycle II, there was a significant increase, with the average score reaching 90.91 and the completeness rate rising to 90.91%. The findings indicate that the application of the Discovery Learning model assisted by Canva effectively enhances students’ ability to write anecdotal texts. Observations and questionnaire results also revealed that students responded very positively to the learning process. This instructional model encouraged students to be more active and independent in their learning. The study reinforces the effectiveness of integrating constructivist learning models with digital media to improve students’ writing skills and recommends that teachers adopt the Discovery Learning approach assisted by Canva to foster active, creative, innovative, and independent writing instruction at various educational levels.